Ferromagnetic elements in two-dimensional materials: 2D magnets and beyond - Papavasileiou, A. V.; Menelaou, Melita; Sofer, Zdeněk; Polavarapu, Lakshminarayana; Mourdikoudis, Stefanos (My University, 2024)
Ferromagnetism in 2D materials has attracted tremendous interest from the scientific community thanks to its potential for the design of magnetic materials with unique properties. The presence of a ferromagnetic element in a 2D material can improve the existing properties and offer new ones, giving rise to the development of manifold applications. This review focuses on recent advances and perspectives of 2D materials that bear at least one ferromagnetic element (iron, cobalt, nickel) as i) structural constituent, ii) dopant atom, or iii) adjacent atom through proximity effect. By describing in detail the magnetic properties that have emerged so far, their potential to form next-generation 2D magnets is discussed. Moreover, the contribution of such 2D materials is analyzed in various applications (electrochemical, photochemical, optical, and electronic), aiming to explore further functionalities and capabilities of ferromagnetic elements, apart from their magnetic nature. Special attention is given to gadolinium and other rare earth elements that display a ferromagnetic order even at ultra-low temperatures and form part of 2D structured materials, with particularly appealing properties deriving from their 4f electrons.